2016
DOI: 10.1093/jb/mvv133
|View full text |Cite
|
Sign up to set email alerts
|

Redox-coupled structural changes in nitrite reductase revealed by serial femtosecond and microfocus crystallography

Abstract: Serial femtosecond crystallography (SFX) has enabled the damage-free structural determination of metalloenzymes and filled the gaps of our knowledge between crystallographic and spectroscopic data. Crystallographers, however, scarcely know whether the rising technique provides truly new structural insights into mechanisms of metalloenzymes partly because of limited resolutions. Copper nitrite reductase (CuNiR), which converts nitrite to nitric oxide in denitrification, has been extensively studied by synchrotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 77 publications
3
34
0
Order By: Relevance
“…S12). Moreover, we recently showed that the imidazole ring of His244 in GtNiR, which corresponds to His255 in AfNiR, rotates as a result of photoreduction, but not the difference of temperatures (55). Therefore, cryogenic temperature would not be the only factor for the rotation and the reduction of Cu may also cause it, as was predicted previously (15).…”
mentioning
confidence: 65%
“…S12). Moreover, we recently showed that the imidazole ring of His244 in GtNiR, which corresponds to His255 in AfNiR, rotates as a result of photoreduction, but not the difference of temperatures (55). Therefore, cryogenic temperature would not be the only factor for the rotation and the reduction of Cu may also cause it, as was predicted previously (15).…”
mentioning
confidence: 65%
“…Little to no change to the overall fold of the enzyme or in the vicinity of the T1Cu site were seen throughout the MSOX series. The low dose atomic resolution starting structure exhibited a previously unseen dual conformation of NO 2 À , in ''top-hat'' and ''side-on'' bidentate orientations, of which the top-hat conformation matches the vertical substrate coordination from 'radiation-damagefree' XFEL structures, 54,58 corroborating the idea that this vertical binding mode represents the initial nitrite binding position. Overall, the 45-dataset MSOX series demonstrated several structural changes at the T2Cu site, Fig.…”
Section: Insights From Multiple-structures One Crystal (Msox) Serial mentioning
confidence: 61%
“…27 Most recently this phenomenon has been exploited to drive in crystallo reactions to generate 'structural movies' of enzyme catalysis in green AcNiR 55,57 and thermostable Geobacillus thermodenitrificans (GtNiR). 58 T2Cu site mutations in AfNiR significantly altered the binding mode of nitrite 21 and these were related to changes in enzyme activity. Mutation of this Ile CAT to Val or Leu led to asymmetric bidentate NO 2 À binding while mutation to Met, Thr, Gly or Ala resulted in monodentate coordination, allowing a water molecule to also bind to T2Cu in a position close to that usually occupied by the O2 atom of nitrite.…”
Section: Substrate Binding To the T2cu Centre And Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Using high photon density in the focused XFEL beam, which achieves single-pulse diffraction within femtosecond exposure time, SFX enables protein structure determination from micrometer-to submicrometer-sized crystals at ambient temperature. The femtosecond pulse duration allows the "diffraction-beforedestruction" approach by circumventing radiation damage of the sample, because the diffraction process can be terminated on a timescale shorter than that of the damage process (4)(5)(6). Moreover, SFX has become a powerful tool for time-resolved analyses of light-driven structural changes and chemical dynamics (7)(8)(9).…”
mentioning
confidence: 99%